(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
Aiming at the requirement of safety test for developing and testing ammunition,the interior ballistic characteristics of high-speed projectile loading device were analyzed. The mechanical property and strength characteristics of barrel structure were considered,and a high-speed fragment launching-device using gunpowder gas driving technology was designed. The device has a diameter of 25 mm and a length of 4 m,and the designed maximum charge is 200 g,and the maximum projectile-mass is 75 g,and the maximum rolling-pressure is 250 MPa. The relationship among the speed,pressure,charge of the device and the mass of the projectile was calculated. The calculation results are consistent with the experimental results. The test results show that the projectile with the mass of 65 g can be launched to 1 840 m/s by using the developed launching device. The controllable loading of high-speed fragments was realized. The study result can be applied to the safety assessment of fragments impact of ammunition.